Triiodothyronine Increases mRNA and Protein Leptin Levels in Short Time in 3T3-L1 Adipocytes by PI3K Pathway Activation - Oliveira, Miriane de [UNESP]; Luvizotto, Renata de Azevedo Melo [UNESP]; Olimpio, Regiane Marques Castro [UNESP]; Sibio, Maria Teresa de [UNESP]; Conde, Sandro José [UNESP]; Biz Rodrigues Silva, Carolina; Moretto, Fernanda Cristina Fontes [UNESP]; Nogueira, Célia Regina [UNESP] (Public Library of Science (PLoS), 2013)
The present study aimed to examine the effects of thyroid hormone (TH), more precisely triiodothyronine (T3), on the modulation of leptin mRNA expression and the involvement of the phosphatidyl inositol 3 kinase (PI3K) signaling pathway in adipocytes, 3T3-L1, cell culture. We examined the involvement of this pathway in mediating TH effects by treating 3T3-L1 adipocytes with physiological (P=10nM) or supraphysiological (SI=100 nM) T3 dose during one hour (short time), in the absence or the presence of PI3K inhibitor (LY294002). The absence of any treatment was considered the control group (C). RT-qPCR was used for mRNA expression analyzes. For data analyzes ANOVA complemented with Tukey's test was used at 5% significance. T3 increased leptin mRNA expression in P (2.26 ± 0.36, p< 0.001), SI (1.99 ±0.22, p< 0.01) compared to C group (1± 0.18). This increase was completely abrogated by LY294002 in P (1.31±0.05, p< 0.001) and SI (1.33±0.31, p< 0.05). Western blotting confirmed these results at protein level, indicating the PI3K pathway dependency. To examine whether leptin is directly induced by T3, we used the translation inhibitor cycloheximide (CHX). In P, the presence of CHX maintained the levels mRNA leptin, but was completely abrogated in SI (1.14±0.09, p> 0.001). These results demonstrate that the activation of the PI3K signaling pathway has a role in TH-mediated direct and indirect leptin gene expression in 3T3-L1 adipocytes. © 2013 Oliveira et al.